Circ-LDLRAD3/miR-655-3p/MAPK1 axis enhances cell migration and invasion in papillary thyroid carcinoma: Circ-LDLRAD3/miR-655-3p/MAPK1 role PTC - Zhang, Bingfei; Peng, Yiquan; Zhou, Lirong (Cellular and Molecular Biology, 2024)
Papillary thyroid carcinoma (PTC) is a prevalent histological subtype of thyroid cancer, whose occurrence and development may be related to circRNA dysregulation. This research proposed to unravel circ-LDLRAD3-related mechanisms in PTC. First, circ-LDLRAD3, miR-655-3p .and MAPK1 levels in PTC were quantitatively measured. Then, plasmid vectors or oligonucleotides that interfere with circ-LDLRAD3, miR-655-3p, or MAPK1 were transfected into PTC cells, followed by the analysis of proliferation, apoptosis, migration, and invasion. Finally, the targeted binding sites between miR-655-3p and circ-LDLRAD3 or MAPK1 were predicted by starBase and experimentally verified. Statistically, PTC samples expressed high circ-LDLRAD3 and MAPK1 and low miR-655-3p. Knocking down circ-LDLRAD3 or enhancing miR-655-3p hindered PTC cell proliferation, migration, and invasion, and forced apoptosis. circ-LDLRAD3 bound to miR-655-3p to affect MAPK1 expression. Elevating MAPK1 rescued circ-LDLRAD3 knockdown-allowed obstruction of PTC cell growth. In conclusion, circ-LDLRAD3 stimulates PTC development by releasing miR-655-3p-targeted MAPK1.